¿«Corruptos» o «eficientes»? La gestión de combustible de la Policía Nacional en Lima - Villaorduña, José Manuel; Bürkli, Hans (Pontificia Universidad Católica del Perú. Fondo Editorial, 2019)
This paper examines cases of illicit fuel use on the part of members of the Peruvian National Police (PNP) in Lima, by regarding the phenomenon as part of the generalized and normalized corruption within the institution. This approach accounts for the failure of the implemented oversight systems to regulate fuel usage and the persistence of irregular practices, such as fuel extraction and unauthorized vehicle use given that these practices have their origin in and in turn uphold structural deficiencies and cultural characteristics of the institution. This research provides an account of the characteristics and mechanisms that allow the generalization of corruption, highlighting those activities that legitimize said practices among members’ narratives. As a result, a positive appraise of illicit fuel use has been constructed in relation to an apparent fulfillment of the institutional mission. Following this approach, traditional definitions of corruption in the public sector and their consequences are problematized here. Information examined in this paper comes from the Direction of Logistics of the PNP (DIRLOG) and from testimonies collected during interviews with members of the organization.

El presente trabajo analiza los casos de uso ilícito del combustible por miembros de la Policía Nacional del Perú (PNP) en Lima, describiendo dicho uso como un fenómeno generalizado y normalizado al interior de la organización. Esta aproximación al problema explicaría por qué, a pesar de la implementación de sistemas de monitoreo y fiscalización del uso de combustible, los casos de sustracción y uso indebido no cesan, en tanto dichas prácticas se originan y sostienen en deficiencias estructurales ycaracterísticas culturales propias de la organización. La investigación procura dar cuenta de cuáles son las características y mecanismos que permiten la generalización de la actividad corrupta, destacando aquellas que legitiman dichas prácticas en las narrativas de sus miembros. Se explica la valoración positiva del uso ilícito del combustible en su aparente funcionalidad para el cumplimiento de la misión organizacional. De esta manera, se problematizan las definiciones tradicionales sobre la corrupción en el sector público y sus consecuencias. Para lograr los objetivos planteados se ha utilizado tanto información proporcionada por la Dirección de Logística de la PNP (DIRLOG) como testimonios recopilados en entrevistas con miembros de la organización.
«Corrupt» or «efficient»? The normalization of the improper use of fuel in the police organization of Lima
Keywords: Corrupción; Policía Nacional del Perú; Normalización; Cultura organizacional; https://purl.org/pe-repo/ocde/ford#5.04.00